Engineering Cellular Resistance to HIV-1 Infection In Vivo Using a Dual Therapeutic Lentiviral Vector - Bryan P Burke; Bernard R Levin; Jane Zhang; Anna Sahakyan; Joshua Boyer; Maria V Carroll; Joanna Camba Colón; Naomi Keech; Valerie Rezek; Gregory Bristol; Erica Eggers; Ruth Cortado; et al. (Molecular Therapy: Nucleic Acids, 2015)
We described earlier a dual-combination anti-HIV type 1 (HIV-1) lentiviral vector (LVsh5/C46) that downregulates CCR5 expression of transduced cells via RNAi and inhibits HIV-1 fusion via cell surface expression of cell membrane-anchored C46 antiviral peptide. This combinatorial approach has two points of inhibition for R5-tropic HIV-1 and is also active against X4-tropic HIV-1. Here, we utilize the humanized bone marrow, liver, thymus (BLT) mouse model to characterize the in vivo efficacy of LVsh5/C46 (Cal-1) vector to engineer cellular resistance to HIV-1 pathogenesis. Human CD34+ hematopoietic stem/progenitor cells (HSPC) either nonmodified or transduced with LVsh5/C46 vector were transplanted to generate control and treatment groups, respectively. Control and experimental groups displayed similar engraftment and multilineage hematopoietic differentiation that included robust CD4+ T-cell development. Splenocytes isolated from the treatment group were resistant to both R5- and X4-tropic HIV-1 during ex vivo challenge experiments. Treatment group animals challenged with R5-tropic HIV-1 displayed significant protection of CD4+ T-cells and reduced viral load within peripheral blood and lymphoid tissues up to 14 weeks postinfection. Gene-marking and transgene expression were confirmed stable at 26 weeks post-transplantation. These data strongly support the use of LVsh5/C46 lentiviral vector in gene and cell therapeutic applications for inhibition of HIV-1 infection.